Benign acute childhood myositis: a retrospective cohort study from a large tertiary care children's hospital - Alghamdi, Nawaf A.; Ajeebi, Abdulaziz A.; Alajlan, Abdulrahman K.; Aldaffaa, Abdullah Y.; Philip, Winnie; Hameed, Tahir K. (Frontiers in Pediatrics, 2025)
IntroductionBenign acute childhood myositis (BACM) is a common self-limiting condition. While studies in other regions have described the epidemiology and outcomes of BACM, there is paucity of data in the Middle East Region. This study aims to describe the epidemiology, clinical data, and outcomes of BACM in a large cohort of patients.MethodsThis was a retrospective cohort study of children diagnosed with BACM at a tertiary care children's hospital between January 2016 and December 2022. The study included children under 14 years with acute onset of muscle pain with elevated CK levels. Clinical, laboratory and outcome data were extracted from the medical records.ResultsA total of 392 children were diagnosed with BACM, with a male predominance (78.6%) and a median age of 6 years. Median CK level at presentation was 1,750 U/L and an Influenza virus was found in 92.8% of those who had a virus detected. Rhabdomyolysis was diagnosed in 4 (1%) patients and no cases of renal failure were reported. CK levels >5,000 U/L on presentation increased the risk for hospitalization while ibuprofen use in the ED decreased the risk of hospitalization. CK levels normalized at a median time of 7 days and recurrences with new episodes of BACM occurred in almost 10% of children.ConclusionsOur study confirms that BACM is a benign condition with a very low rate of complications. Further studies are needed to evaluate factors associated with hospitalization and when to screen for genetic/metabolic causes of elevated CK levels.